Stress fractures in the distal humerus of elite tennis players - Wood, T. (Medicine and Science in Tennis, 2003)
Pain syndromes around the elbow in elite tennis players are common. Flexor or extensor tendinopathy (medial and lateral epicondylitis) are well known to us all. However, recently it has become apparent that there are a significant numbers of players presenting with a different pattern of pain from a different source.